Bjårskpip in Blossom: On the Revitalization Process of a Folk Music Instrument - Lundberg, Dan (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2007)
Daniel Danielsson was a man with many, and varied, occupations in Laxviken, Jämtland. He worked as timber-floater, but was also a talented blacksmith, woodturner, and stonecutter. Danielsson also applied his talents in different musical contexts. He played the cornet in the village brass ensemble and often performed at home together with the church organist. Sometime at the turn of the twentieth century, he started to make flutes; we don’t know how many, but today five instruments are known. Danielsson’s flute project was a success even if he himself was not totally content with the result. After his death in 1937, the flutes remained on his farm and were used by his grandchildren. As they grew up and moved to other places they brought the flutes with them as heirlooms and they were kept in bookshelves and drawers, or hung on walls. In recent years, Danielsson’s flutes have been brought back to life through the efforts of the flute maker Gunnar Stenmark. In a way, this is a true revival, because the flutes were essentially dead, unused, for many decades. Noone really knows how long the flutes were in the hands of Danielsson himself. But with the help of Norwegian models and recordings of flute playing in Sweden, we can recreate a trustworthy playing technique for the instrument. This article examines the different roles of various actors in a revival process. With Daniel Danielsson’s flute as an example, we can make a simplified division between the roles of the researcher, the flute maker and the musician in the revival process. The flute maker’s primary goal is to enlarge his assortment of flutes. His goal differs from that of the ethnomusicologist whose aims have to do with understanding how the instrument functions, in what contexts it was used, how it was built, and what the prototypes might have been, etc. The musician, on his or her side, puts music making first and is most interested in a useful and flexible instrument.